Metformin raises hydrogen sulfide tissue concentrations in various mouse organs - Wiliński, Bogdan; Wiliński, Jerzy; Somogyi, Eugeniusz; Piotrowska, Joanna; Opoka, Włodzimierz (Pharmacological reports, 2013)
The epidemic of diabetes mellitus type 2 forces to intensive work on the disease medication. Metformin, the most widely prescribed insulin sensitizer, exerts pleiotropic actions on different tissues by not fully recognized mechanisms. Hydrogen sulfide (H2S) is involved in physiology and pathophysiology of various systems in mammals and is perceived as a potential agent in the treatment of different disorders. The interaction between biguanides and H2S is unknown. The aim of the study is to assess the influence of metformin on the H2S tissue concentrations in different mouse organs. Adult SJL female mice were administered intraperitoneally 100mg/kg b.w. per day of metformin (group D1, n=6) or 200mg/kg b.w. per day of metformin (group D2, n=7). The control group (n=6) received physiological saline. The measurements of the free and acid-labile H2S tissue concentrations were performed with Siegel spectrophotometric modified method. There was a significant progressive increase in the H2S concentration along with the rising metformin doses as compared to the control group in the brain (D1 by 103.6%, D2 by 113.5%), in the heart (D1 by 11.7%, D2 by 27.5%) and in the kidney (D1 by 7.1%, D2 by 9.6%). In the liver, massive H2S accumulation was observed in the group D1 (increase by 420.4%), while in the D2 group only slight H2S level enhancement was noted (by 12.5%). Our experiment has shown that metformin administration is followed by H2S tissue concentrations increase in mouse brain, heart, kidney and liver.